CLIL: A New Trend Of Teaching English To Engineering Students (Journal of Namibian Studies : History Politics Culture, 2022)
CLIL, which stands for "Content and Language Integrated Learning," is a method of teaching content areas to students who are learning English as a second (or even third) language. Using a language that is not the student's mother tongue as a medium of instruction and assessment, CLIL is an innovative approach to education. The process of acquiring knowledge and skills across the curriculum is made more challenging and time-consuming when taught in a language other than one's mother tongue. While content-based integrated learning (CLIL) is extensively used in K-12 settings, this is not always the case in higher education. The primary focus of technical institutions is on the acquisition of engineering knowledge (content) in a variety of sub-disciplines. The ability to speak multiple languages and communicate effectively is becoming increasingly important for technical college grads in today's competitive employment environment.The use of CLIL in the classroom is cutting edge at the moment. It is when a class is taught in a language other than the one spoken at home. Languages other than English are often taught using CLIL. Learning English as a second language is popular in India. The primary goal of this paper is to evaluate the effectiveness of CLIL training that incorporates technology in an Indian engineering college setting.